How to write a manuscript for Sports Engineering - Allen, T.; Blocken, B.; Drory, A.; Espinosa, H. G. (Sports Engineering, 2020)
This editorial provides guidance for authors preparing a manuscript for submission to Sports Engineering. It does not replace the submission guidelines on the journal webpage,Footnote1 nor does it simply duplicate the scientific paper writing guides that are already available [1,2,3,4,5,6,7,8]. The submission guidelines on the journal webpage provide specific instructions that authors must adhere to, including details on article types and associated word and figure/table limits, how the manuscript should be formatted and structured and referencing style. The submission guidelines are periodically reviewed and updated as required.